Heart rate variability after sprint interval training in cyclists and implications for assessing physical fatigue - Hebisz, R. G.; Hebisz, P.; Zaton, M. W. (The Journal of Strength and Conditioning Research, 2022)
This study evaluated the time- and frequency-domain indexes of heart rate variability (HRV) during sprint interval exercise test (SIXT) and identify the onset of fatigue by HRV concurrent with changes in average (Pavg) and peak (Ppeak) power output, total oxygen uptake (VO2tou), and blood hydrogen (H+) and lactate (La-) concentrations. Twenty-seven cyclists performed 4 sets of SIXT in which each set consisted of four 30-second maximal sprints interspersed with 90 seconds of low-intensity cycling. Each set was separated by 25-40 minutes of recovery. Before beginning each set, HRV was analyzed by time (mean normal-to-normal RR intervals [RRNN], SD of normal-to-normal RR intervals [SDNN], and square root of the mean squared difference between successive normal-to-normal RR intervals [RMSSD]) and frequency (total spectral power [T] and very low- [VLF], low- [LF], and high-frequency [HF] spectral power) domain methods. Pavg, Ppeak, and VO2tou were recorded in each set, and H+ and La- were measured after each set. RRNN, SDNN, and VLF decreased in the second set, whereas all time and frequency indexes of HRV decreased in the third and fourth set. Pavg and H+ decreased, while VO2tou increased in the fourth set. Ppeak decreased in the second, third, and fourth set. Correlations were found between the changes in the time and frequency indexes of HRV with H+, La-, and VO2tou. The results indicate that HRV does not reflect the onset of physical fatigue in SIXT as was observed in Pavg and no correlation was found between the changes in HRV with Pavg and Ppeak.